Linguistic Manipulation in Political Discourse Based on the Speeches of Vladimir Putin - Chałagus, Kacper (The phenomena of propaganda and manipulation in the press, radio, television, and internet. Volume III, 2025)
The article is an attempt to analyze the problem of linguistic manipulation in political discourse. As the research material, two speeches by Vladimir Putin published on YouTube in the early phase of Russia’s invasion of Ukraine in 2022 were used. In the course of the research, a qualitative analysis was conducted, based on the theory of persuasive metaoperators by Prof. Aleksey Avdeyev, including the division of linguistic means of influence into four independent groups: metaoperators blocking verification, metaoperators causing the “observer effect,” metaoperators changing the hierarchy of the informational system, and metaoperators strengthening pragmatic functions. The article also describes the role of linguistic means of influence in the general concept of political discourse. As a result of the research, the dominant persuasive strategies used by Vladimir Putin were described, including the emphasizing of personal and possessive pronouns in plural forms at the prosodic level and the use of constructions referring to unquestionable concepts such as “fact.”